Pengaruh pemberian pupuk organik cair limbah kulit udang (Panaeus monodon l.) terhadap produksi tanaman kacang panjang (Vigna sinensis l.) - Rusnaini Rusnaini; Wuriesyliane Wuriesyliane; Rezi Perdana (Universitas Muhammadiyah Mataram, 2023)
This study aim was to determine the effect of liquid organic fertilizer from shrimp shell waste (Panaeus monodon L.) on the production of long bean (Vigna sinensis L.). The method used in this study was a randomized block design (RBD) method which consisted of six treatments, namely POC waste tiger prawn shells P0 = 0 ml/plant, P1 = 25 ml/plant, P2 = 50 ml/plant, P3 = 75 ml/plant. plants, P4 = 100 ml/plant, and P5 = 125 ml/plant and repeated four times. The experimental results showed that the application of POC from tiger prawn shell waste (P) showed a very significant effect on plant height (cm), fresh weight of plants, number of pods and pod weight of long bean plants and had no significant effect on flowering time of long bean plants. The higher the concentration of the application of the search fertilizer, the better the growth and yield of the plants and the highest was in Treatment P4 (100 ml/plant) resulting in plant height, plant fresh weight, number of pods and pod weight each with an average value of 171.05 cm , 194.00 g, 14.88 pieces and 197.00 g. The fastest flowering age was in the P5 treatment (125 ml/plant) with an average value of 29.00 days. The application of liquid organic fertilizer from shrimp shell waste shows optimum growth and yield at a concentration of 100 ml/plant.